Economics : an analytical introduction - Witztum, Amos. (Oxford ; New York : Oxford University Press, 2005)
It delivers a focused view of the logical core of economic analysis, and teaches students to apply theories and models to recognisible, real-life examples.
Includes bibliographical references and index.
uaj 26/02/2015
Loans
Keywords: Economics